Policy Analysis of the Freedom Curriculum to Create Excellent Education - Rahmi, Ranianisa; Rusdinal, Rusdinal; Hadiyanto, Hadiyanto (International Journal of Educational Dynamics, 2023)
An excellent education can mature pupils' qualities as they mature by releasing them from ignorance and ineptitude. Generations of people with exceptional human resources will be born as is, thanks to excellent education, in all aspects. A feature of life. The government has implemented numerous initiatives to raise the standard of education, including the autonomous learning policy. Educational institutions are not any less lagging behind in terms of raising the standard of instruction, namely by keeping up with improvements in both the human resource base and the standard of instruction. A qualitative method descriptive analytic methodology was employed in this study, and the study's goal was to characterize the autonomous learning policy as a whole.